UPAYA UNIT BINPOLMAS MELALUI PENINGKATAN KINERJA BHABINKAMTIBMAS DALAM MENCEGAH CURAT GUNA MEWUJUDKAN HARKAMTIBMAS DI WILAYAH HUKUM POLRES TEGAL KOTA - Azriel Munandar (Indonesian Journal of Police Studies, 2022)
ABSTRACT THE EFFORTS OF THE BINPOLMAS UNITS THROUGH BHABINKAMTIBMAS IN PREVENTING BURGLARRY IN THE JURISDICTION OF THE TEGAL CITY POLICE Azriel Alie Ibrahim Munandar, 18.080, azrielmunandar14@gmail,com The background that underlies the research starts from the main duties of the National Police listed in Article 13 of Law No. 2 of 2002 concerning the National Police of the Republic of Indonesia, to realize this preventive action through partnership activities carried out by the Binpolmas Unit through Bhabinkamtibmas. One of the kamtibmas disturbances that occurred was the crime of theft with a ballast where curated crime dominated in the jurisdiction of tegal city police. This research uses a qualitative approach as well as a type of field approach with a focus on the efforts of the Binpolmas Unit in improving the performance of Bhabinkamtibmas. In the research literature research took references from 3 different people with differences and similarities respectively as well as with the novelty of writing this final project. Conceptual literature used with 6 concepts and 2 theories, namely management theory and competence. Factual conditions describe how the implementation of the Binpolmas Unit through Bhabinkamtibmas in establishing partnerships and Efforts of Unti Binpolmas in improving the performance of Bhabinkamtibmas and the existence of factors that affect both internally and externally. Based on the factual conditions that occurred and with the conditions expected to be guided by Perpol number 1 of 2021 concerning polmas and Perkap number 7 of 2021 concerning Bhabinkamtibmas, problem solving was arranged related to the implementation of the Binpolmas Unit and the Efforts of the Binpolmas Unit in improving the performance of Bhabinkamtibmas by using a knife analysis of concepts and theories that have been determined. Based on these problem-solving measures, it can be concluded that the implementation of the partnership established by Bhabinkamtibmas has not been going well and the need to improve bhabinkamtibmas performance is guided by Perpol number 1 of 2021 concerning Polmas. So it is also given advice on the implementation of partnerships and efforts to improve the performance of Bhabibnkamtibmas.